1985
DOI: 10.1016/0020-7292(85)90103-1
|View full text |Cite
|
Sign up to set email alerts
|

Trends in neonatal mortality in Benin City, Nigeria

Abstract: A total of 18,334 live births and 376 neonatal deaths at the University of Benin Teaching Hospital were analyzed. The neonatal mortality rate has declined significantly from 49.5/1000 in 1974 to 16.4/1000 live births in 1981. The decrease mainly resulted from the reduction of mortality of full size infants (greater than 2500 g) and deaths resulting from perinatal asphyxia. Further reduction may be anticipated if careful attention is paid to the management of breech delivery and if a more intensive care for low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
2
8
0
1
Order By: Relevance
“…However, poor parental knowledge of important aetiological factors of neonatal hearing loss such as jaundice and birth asphyxia is noteworthy. This is a reflection of the deficiency in current health education given to mothers during antenatal care despite documented reports about these risk factors [11,12]. Furthermore a causal relationship has been established between traditional medicine and childhood convulsions [13].…”
Section: Discussionmentioning
confidence: 97%
“…However, poor parental knowledge of important aetiological factors of neonatal hearing loss such as jaundice and birth asphyxia is noteworthy. This is a reflection of the deficiency in current health education given to mothers during antenatal care despite documented reports about these risk factors [11,12]. Furthermore a causal relationship has been established between traditional medicine and childhood convulsions [13].…”
Section: Discussionmentioning
confidence: 97%
“…5 A study by Okolo and Omene in Benin city showed that neonatal mortality was reduced from 49.5/1000 live births to 16.4/1000 from the 1974 to 1981 just by the reduction of birth asphyxia in term neonates. 11 This could be unavailability of skilled attendant at the time of delivery at home. Increasing the percentage of births delivered in health facilities is important for reducing deaths due to asphyxia which ultimately help to reduce the neonatal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 133 million children born annually worldwide, over 4 million are likely to die within the first 28 days of life 1,2 . While maternal and child health care in developed countries have witnessed substantial improvements in the last three decades, 3 perinatal care in most of the developing world (which accounts for 90% of global births) is still characterised by a range of adverse conditions such as (but not limited to) young maternal age, prolonged and obstructed labour (pre)eclampsia, breech and multiple deliveries, prolonged rupture of membranes, low birthweight, birth asphyxia, jaundice, sepsis, seizures, stillbirths, neonatal and maternal deaths 2,4–6 . The preventive value of programmes aimed at high immunisation uptake, improved personal hygiene, safer antenatal/delivery care and better health education has been acknowledged globally and continues to attract attention from governments, donor agencies and various multilateral institutions.…”
Section: Introductionmentioning
confidence: 99%